2007
DOI: 10.1108/17465729200700003
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to stop smoking support for people with mental health problems

Abstract: The physical health inequalities experienced by people with severe mental health problems are now well recognised. Lifestyle factors, in particular high rates of smoking, have been identified as a major contributor to the raised mortality and morbidity in this population. A programme was developed in West Surrey to address smoking cessation support needs in people with mental health problems. Mental health workers were trained to deliver stop smoking support and a pilot programme of oneto-one stop smoking supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Training for leisure facilities staff was suggested as a possible route to overcome this issue. Qualitative interviews with seven mental health service users who received one‐to‐one smoking cessation support also highlighted the personal characteristics of the advisor, a positive approach, good listening skills and knowledge about mental health issues were typical of advisors who were able to encourage individuals to engage with the intervention (Edmonds & Bremner 2007). In addition, individually tailored interventions are also reported to encourage engagement with an intervention (Fogarty & Happell 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training for leisure facilities staff was suggested as a possible route to overcome this issue. Qualitative interviews with seven mental health service users who received one‐to‐one smoking cessation support also highlighted the personal characteristics of the advisor, a positive approach, good listening skills and knowledge about mental health issues were typical of advisors who were able to encourage individuals to engage with the intervention (Edmonds & Bremner 2007). In addition, individually tailored interventions are also reported to encourage engagement with an intervention (Fogarty & Happell 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Participants valued a group intervention with motivational leadership according to the focus group study by McDevitt et al (2006). However, in a qualitative study by Edmonds and Bremner (2007) on oneto-one support for smoking cessation in people with mental health problems, group support was less favoured by mental health professionals because: groups were thought to be overused in mental health services; support is not individualized; it would be difficult to maintain focus on smoking cessation in a group context; and it would be difficult to find sufficient numbers to form a group in one mental health setting. However, where there was support for group-based smoking cessation intervention it was suggested that it should be specifically for mental health service users.…”
Section: Incentives To Participationmentioning
confidence: 99%
“…). Some authors suggest that group‐based interventions are overused in mental health care (Edmonds & Bremner ). Our evidence supports the delivery of group‐based health promotion interventions for this clinical group by providing a social context in which the service user can flourish.…”
Section: Discussionmentioning
confidence: 99%
“…Research with service users suggest that over half of those who smoke would like to quit, but many do not receive support to access stop smoking services. In West Surrey a survey of service users found that 59% of those who smoked had never been advised to quit by a health professional, although 59% actually wanted to quit (Edmonds & Bremner, 2006).…”
Section: Supporting People With Mental Health Problems To Quit Smokingmentioning
confidence: 99%
“…As this specialised one-to-one support was a new approach to helping people with mental health problems to quit smoking, the programme was evaluated and the findings published (Edmonds & Bremner, 2007).…”
Section: Stop Smoking Supportmentioning
confidence: 99%